2016
DOI: 10.2989/16085914.2016.1169988
|View full text |Cite
|
Sign up to set email alerts
|

Population parameters and exploitation rate ofSarotherodon galilaeus galilaeus(Cichlidae) in Lakes Doukon and Togbadji, Benin

Abstract: Growth, mortality, recruitment and relative yield per recruit of Sarotherodon galilaeus galilaeus from Lakes Doukon and Togbadji were studied. Data on total length, total weight and sex were recorded on a monthly basis between January and December 2013 for S. g. galilaeus captured by local fishers. The estimated asymptotic lengths L" were 26.2 and 23.6 cm for Lakes Doukon and Togbadji, respectively, while the growth rate K was 0.73 in Lake Doukon and 0.87 in Lake Togbadji. Estimates of fishing mortality, 0.27 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 17 publications
2
12
1
1
Order By: Relevance
“…sector of Ghana. However, studies on the same species in Doukon and Togbadji reservoirs in Benin by Lederoun et al (2016) depict a larger asymptotic length, while the K estimates are comparable to those reported in this study (Table 8). The growth parameters of the target species estimated in our study are also similar and comparable to those reported for C. zillii and O. niloticus in a previous study of the Bontanga Reservoir by Ofori-Danson et al (2008) but differ for S. galilaeus.…”
Section: Growth Parameter Estimatessupporting
confidence: 84%
See 1 more Smart Citation
“…sector of Ghana. However, studies on the same species in Doukon and Togbadji reservoirs in Benin by Lederoun et al (2016) depict a larger asymptotic length, while the K estimates are comparable to those reported in this study (Table 8). The growth parameters of the target species estimated in our study are also similar and comparable to those reported for C. zillii and O. niloticus in a previous study of the Bontanga Reservoir by Ofori-Danson et al (2008) but differ for S. galilaeus.…”
Section: Growth Parameter Estimatessupporting
confidence: 84%
“…The desirable target would be to let as many fish as possible spawn at least once before they are caught, to rebuild and maintain healthy spawning stocks (Froese 2004). The total length at first sexual maturity was based on published research on the species (Adite and Van Thielen 1995, Akongyuure et al 2017b, Duponchelle and Panfili 1998, Kwarfo-Apegyah and Ofori-Danson 2010, Lederoun et al 2016, Ofori-Danson et al 2008.…”
Section: Relative Yield Per Recruit (Y'/r) and Reference Pointsmentioning
confidence: 99%
“…The results of the current study do not differ greatly from those of Lederoun et al . (), who reported the sizes at first sexual maturity of female S. galilaeus were 12.8 cm in Lake Doukon and 11.5 cm in Lake Togbadji in Benni. In contrast, the results of the present study disagreed with those of Adams et al .…”
Section: Discussionmentioning
confidence: 99%
“…Benin is a coastal country with a river-rich watershed, especially in its southern part. The SÔ River, located northwest of Nokoué Lake in the municipality of Sô-ava, like the other rivers of the country, is subject to the action of local populations whose main activity is fishing (Lederoun et al, 2016).…”
mentioning
confidence: 99%
“…However, the widespread use of non-regulatory fishing gear, techniques and fishing methods is leading to the degradation of aquatic ecosystems. Fishing is one of the causes of the degradation of river biodiversity (Lederoun et al, 2016. The intensification of the exploitation of freshwater and brackish water populations by permanently growing local populations constitutes a major risk of regression and disappearance of species (Kouakou et al, 2016, Aholoukpe, 2017.…”
mentioning
confidence: 99%